Spectral and molecular modeling studies on the influence of β-cyclodextrin and its derivatives on aripiprazole-human serum albumin binding. (20th October 2015) - Yan, Jin; Wu, Di; Ma, Xiaoli; Wang, Lili; Xu, Kailin; Li, Hui
Highlights: Binding between aripiprazole (APZ) and HSA was studied mainly by fluorescence method. Effect of three CyD on APZ–HSA binding was studied by fluorescence, CD, UV–vis, NMR. The results indicate β-CyD has the largest impact on inhibiting APZ–HSA interaction. 1:1 Inclusion complex between APZ and three CyD is one of the reasons of influence. CyD incorporating amino acids on the surface of HSA is another reason of influence. Abstract: The binding mechanism of aripiprazole (APZ) with human serum albumin (HSA) in the absence and presence of three cyclodextrins (CyDs) (β-cyclodextrin, hydroxypropyl-β-cyclodextrin, and (2, 6-di- O -methyl)-β-cyclodextrin) was studied by fluorescence, ultraviolet–visible absorption, nuclear magnetic resonance, and circular dichroism (CD) spectroscopy. The CD results revealed some degree of recovery of refolding caused by APZ after the addition of CyD. The Stern–Volmer quenching constant and binding constant of the APZ–HSA interaction were smaller in the presence of the three CyDs. The ultraviolet–visible absorption results indicated that APZ formed 1:1 complex with the three CyDs. The 1 H NMR spectra of CyD showed chemical shift and resolution loss of proton after the addition of HSA. Molecular modeling studies showed that both APZ and CyD bind to HSA. The process was initiated through inclusion of free APZ molecules by CyD and the increase in steric hindrance of CyD–HSA binding.